(untitled) (Student’s Journal of Health Research Africa, 2026)
Background Postgraduate supervision is expected to foster academic growth, ethical research practice, and intellectual independence. However, supervisory relationships may also become sites of power abuse, where manipulative behaviours undermine student autonomy, delay academic progress, and negatively affect well-being. This study explored manifestations of manipulative supervision within South African higher education institutions and examined their implications for postgraduate students and research ethics. Methods A qualitative multi-case study was conducted at two public universities between February and April 2024. A purposive sample of 24 participants was selected, comprising 14 postgraduate students (8 Master’s and 6 PhD candidates) and 10 academic supervisors from the faculties of Science, Education, and Social Sciences. Data were generated through 18 semi-structured in-depth interviews and two focus group discussions. The data were analysed using Braun and Clarke’s six-step thematic analysis framework. Results Four interrelated themes emerged. First, academic gatekeeping was evident through delayed feedback, excessive revisions, and shifting expectations, which students perceived as mechanisms to control progression. Second, exploitation of student research was reported, with students describing pressure to include supervisors as authors or to prioritise supervisors’ publication agendas over their own research goals. Third, emotional manipulation and favouritism manifested through selective support, intimidation, and conditional approval, contributing to anxiety, self-doubt, and isolation among students. Finally, a lack of institutional recourse was identified, as students expressed fear of retaliation and limited confidence in existing grievance mechanisms. Some supervisors acknowledged power imbalances but framed these practices as necessary for academic rigor and training. Conclusion Manipulative supervisory practices, whether intentional or normalized, undermine postgraduate development, ethical research conduct, and student well-being, and contribute to the persistence of inequitable academic cultures. Recommendations Clear supervision guidelines, transparent supervisory agreements, regular feedback channels, and stronger institutional accountability mechanisms are essential to promote ethical, supportive, and transformative postgraduate supervision environments.